PENGARUH IMPLEMENTASI RELATIONSHIP MARKETING TERHADAP LOYALITAS PELANGGAN PADA AUTO 2000 CABANG SUTOYO MALANG - Hemayanti, Nadia Ayu; anto, Subi (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aims to determine how much influence Relationship Marketing is comprised of mutual advantage (X1), commitment (X2), truth (X3), and communication (X4) on customer loyalty in AUTO 2000 SUTOYO Malang. To determine how much influence the independent variables (independent variables) on the dependent variable (dependent variable) used multiple regression analysis to test methods and test F T. This research includes explanatory research, which describes the relationship and influence of independent variables on the dependent variable. The population in this study are all consumers AUTO2000 SUTOYO Malang branch and samples taken 140 respondents. The results showed that simultaneous dimensions of mutual benefit (X1), commitment (X2), truth (X3), and communication (X4) significantly influence customer loyalty with a significance value of 0.000 and a coefficient R2 of 0.582. Partially dimensional mutual benefit (X1), commitment (X2), truth (X3), and communication (X4) significantly influence customer loyalty with three significant value <α = 0.05. Is the dominant variable affecting the truth variable (X3) with standardized beta coefficients of 0.351. Keywords: Relationship Marketing, Customer Loyalty